DESAIN SISTEM ANTRIAN PELANGGAN BARBERSHOP - Juan Philbert Artori Kris; Kris, Juan Philbert Artori; Lahallo, Jim (Jurnal Ilmiah Sistem Informasi, 2025)
Manual queuing systems at barbershops often lead to inefficiencies, such as long lines and recording errors, which can result in customer dissatisfaction. This research aims to design and implement a ticket-based queuing system similar to those used in banks. In this system, customers take a ticket number and are called according to the number they took. Methods used in this study include a user needs analysis to understand customer expectations and problems and system design using flowcharts and the Unified Modeling Language (UML) to visualize system processes and interactions. The system was implemented using a Raspberry Pi as the main controller and a thermal printer to print queue tickets. Results showed that the new system reduced customer waiting time by 40%, compared to the previous manual system. Additionally, a user satisfaction survey revealed a significant improvement, with 85% of customers expressing greater satisfaction with their queuing experience. In conclusion, the ticket-based queuing system effectively optimized barbershop operations, improved service efficiency, and provided a better customer experience. This research is expected to serve as a reference for other barbershops looking to improve their queuing systems and provide better service.